Providing information about a child's oncological disease - a challenge for a pediatric oncologist - Piotr Pawłowski; Karolina Ziętara; Justyna Michalczyk; Magdalena Fryze; Aneta Kościołek (Nicolaus Copernicus University in Toruń, 2023)
Introduction: The diagnosis of a serious illness in a family affects all members. The child is a special subject, as he cannot yet understand many aspects of life at such a high perceptual level as an adult. Communicating difficult information is part of the doctor's task and is one of the most difficult parts of the therapeutic process.  The aim of the study: To analyze the methodology of communicating difficult information to pediatric oncology patients. Material and method: Polish and English-language scientific literature from 2012 - 2022 from databases such as PubMed, SCOPUS, Google Scholar, Web of Science was reviewed. Searches were conducted according to keywords: communicating difficult information, oncology, pediatrics, physician. Results and conclusions: One of the most well-known protocols for communicating difficult information is SPIKES. It describes the basic and necessary steps for properly informing parents and the child about the diagnosis, for example. Healthy siblings should also learn about their brother's illness, but this task falls to the parents. Psycho-oncological support for both the child and parents should be holistic, based on best practices, and tailored to the family's needs.